Immunotherapeutic Synergy Between Anti-CD137 mAb and Intratumoral Administration of a Cytopathic Semliki Forest Virus Encoding IL-12 - Quetglas, José I (Nature Publishing Group, 2012)
Intratumoral injection of Semliki Forest virus encoding interleukin-12 (SFV-IL-12) combines acute expression of IL-12 and stressful apoptosis of infected malignant cells. Agonist antibodies directed to costimulatory receptor CD137 (4-1BB) strongly amplify pre-existing cellular immune responses toward weak tumor antigens. In this study, we provide evidence for powerful synergistic effects of a combined strategy consisting of intratumoral injection of SFV-IL-12 and systemic delivery of agonist anti-CD137 monoclonal antibodies (mAbs), which was substantiated against poorly immunogenic B16 melanomas (B16-OVA and B16.F10) and TC-1 lung carcinomas. Effector CD8(β)(+) T cells were sufficient to mediate complete tumor eradications. Accordingly, there was an intensely synergistic in vivo enhancement of cytotoxic T lymphocytes (CTL)-mediated immunity against the tumor antigens OVA and tyrosine-related protein-2 (TRP-2). This train of phenomena led to long-lasting tumor-specific immunity against rechallenge, attained transient control of the progression of concomitant tumor lesions that were not directly treated with SFV-IL-12 and caused autoimmune vitiligo. Importantly, we found that SFV-IL-12 intratumoral injection induces bright expression of CD137 on most tumor-infiltrating CD8(+) T lymphocytes, thereby providing more abundant targets for the action of the agonist antibody. This efficacious combinatorial immunotherapy strategy offers feasibility for clinical translation since anti-CD137 mAbs are already undergoing clinical trials and development of clinical-grade SFV-IL-12 vectors is in progress.